Type I diabetes mellitus decreases in vivo macrophage-to-feces reverse cholesterol transport despite increased biliary sterol secretion in mice - Freark de Boer, Jan (The American Society for Biochemistry and Molecular Biology, 2012)
Type I diabetes mellitus (T1DM) increases atherosclerotic cardiovascular disease; however, the underlying pathophysiology is still incompletely understood. We investigated whether experimental T1DM impacts HDL-mediated reverse cholesterol transport (RCT). C57BL/6J mice with alloxan-induced T1DM had higher plasma cholesterol levels (P < 0.05), particularly within HDL, and increased hepatic cholesterol content (P < 0.001). T1DM resulted in increased bile flow (2.1-fold; P < 0.05) and biliary secretion of bile acids (BA, 10.5-fold; P < 0.001), phospholipids (4.5-fold; P < 0.001), and cholesterol (5.5-fold; P < 0.05). Hepatic cholesterol synthesis was unaltered, whereas BA synthesis was increased in T1DM (P < 0.001). Mass fecal BA output was significantly higher in T1DM mice (1.5-fold; P < 0.05), fecal neutral sterol excretion did not change due to increased intestinal cholesterol absorption (2.1-fold; P < 0.05). Overall in vivo macrophage-to-feces RCT, using [(3)H]cholesterol-loaded primary mouse macrophage foam cells, was 20% lower in T1DM (P < 0.05), mainly due to reduced tracer excretion within BA (P < 0.05). In vitro experiments revealed unchanged cholesterol efflux toward T1DM HDL, whereas scavenger receptor class BI-mediated selective uptake from T1DM HDL was lower in vitro and in vivo (HDL kinetic experiments) (P < 0.05), conceivably due to increased glycation of HDL-associated proteins (+65%, P < 0.01). In summary, despite higher mass biliary sterol secretion T1DM impairs macrophage-to-feces RCT, mainly by decreasing hepatic selective uptake, a mechanism conceivably contributing to increased cardiovascular disease in T1DM.